Application of model predictive control to batch polymerization reactor - Ghasem, N.M.; Hussain, Mohd Azlan; Sata, S.A. (Revista de la Facultad de Ciencias, 2006)
The absence of a stable operational state in polymerization reactors that operates in batches is factor that determine the need of a special control system. in this study advanced control metodology is implemented for controlling the operation of a batch polimerization reactor for polystyrene production utilizing model predective control. By utilizing a model of the polimerization process, the necessary operational conditonal were determined for producing the polymer within the desired characteristics. The main control objective is to bring the reactor temperature to its target temperature rapidly as posible with minimal temperature overshoot. Control performance for the proposed method is encouraging. It has been observed that temperature overshoot can be minimized by the proposed method with the use of both reactor and jacket energy balance for reactor temperature control.